Analysis of Empty Box Victory in Makassar City Regional Head Elections in 2018 - Casa Sulthan Mulya; Indiana Ngenget; Musthofa Musthofa (Budapest International Research and Critics University, 2022)
This study analysis of empty box victory in Makassar City regional head elections in 2018. The approach used in this research is qualitative. Data collection techniques with in-depth interviews and literature study. The results showed that a single candidate against an empty box victory occurred in Makassar City regional head elections in 2018, after the Danny-Indira candidate pair was disqualified for alleged money politics. The empty box victory has relevance to the disqualification of Danny Pomanto as the incumbent when the regional head elections were already underway so that the winning team and supporters networks had been formed concretely, the spread of Danny Pomanto's support network was unavoidable and interest groups supporting empty boxes like Rewako were ready to accommodate and accommodate they. The attitude of domination politics and the use of identity politics by Appi-Cicu in the middle of an industrial and service city also plays a role in venting public antipathy and venting their choices into empty boxes.